Membrane type dialyzer with high permeability and selectivity and preparation method
By using polyether sulfone and dry-wet spinning technology in the hemodialyzer, a membrane dialyzer with a pore size of 8~12nm was prepared, which solved the problem of insufficient scavenging ability of medium-toxins in the prior art, achieved higher permeability and selectivity, and improved the patient's health status.
Patent Information
- Application Number
- CN202510137649.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing hemodialyzers have limited ability to remove medium-macro toxins, and the membrane pore size is too small to effectively remove medium-macro toxins in patients' bodies.
A combination of polyether sulfone, pore-generating agent, solvent, additive and water was used to prepare a membrane dialyzer through dry-wet spinning technology, and the membrane pore size was controlled to increase the permeability and selectivity of the membrane.
It has achieved effective removal of medium-macromolecular toxins, improved the health status of long-term dialysis patients, reduced albumin loss, and has good biocompatibility and selectivity.
Smart Images

Figure CN119793250A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dialyzer membranes, and in particular to a high-permeability and high-selectivity membrane-type dialyzer and a preparation method thereof. Background Art
[0002] Hemodialysis technology is an important way of renal replacement therapy for patients with acute and chronic renal failure. It drains the blood in the human body to the outside of the body, purifies the blood through the dialyzer, and returns the purified blood to the human body. The membrane used in the hemodialyzer uses the principle of a semi-permeable membrane. With the help of the solute gradient, osmotic gradient and water pressure gradient on both sides of the membrane, it can remove toxins and excess water in the body, replenish the substances needed by the body, and maintain the acid-base balance of electrolytes.
[0003] The key element of hemodialysis technology is its excellent membrane pore screening characteristics, and the size of the pore size is the determining factor of its membrane pore screening capacity. Among them, low-flux hemodialysis has a good removal effect on small molecule toxins, but has limited removal of solutes with a molecular weight >1KDa; high-flux hemodialysis can only remove toxins with a molecular weight <15KDa; hemodiafiltration combines diffusion and convection to improve the clearance rate of substances with a molecular weight of up to 25KDa, but there are still many toxins whose molecular size exceeds the pore size range of the semipermeable membrane that cannot be filtered. For example, α1-microglobulin is a glycoprotein pro-inflammatory factor in the human body, chitinase protein-40 (YKL-40), with a molecular weight of 40K Daltons, and λ free light chain (λ-FLC) is a monoclonal immunoglobulin secreted by plasma cells, with a molecular weight of 45K Daltons. Ordinary dialyzers have certain limitations in the removal of these macromolecules, so hemodialysis membranes with larger pores are needed.
[0004] The common low-flux hemodialyzer has a membrane pore size of 1~3 nm, which can generally remove small molecular weight substances with a molecular weight of less than 500 Daltons; the high-flux dialyzer has a membrane pore size of about 5~8 nm, which can generally remove substances with a molecular weight of 500~5000 Daltons. Therefore, to filter medium and large molecular toxins with a molecular weight greater than 25KDa, or even up to 45KDa, the pore size of the hemodialysis membrane must be at least 8nm, and in order to ensure better selectivity and permeability of the membrane, the pore size of the membrane must be uniform. Since the pore size of the membrane is too large, it will cause the loss of albumin necessary for the human body. Therefore, in the preparation of this hemodialysis membrane with a large and uniform pore size, the loss of albumin needs to be controlled within the range that the human body can bear. Since the pore size of this dialysis membrane is larger than that of a general dialyzer, the HD treatment mode can be used instead of the HDF treatment mode during treatment. This is mainly due to the large pore size of the membrane and the slightly smaller fiber inner diameter, which can form an internal filtration phenomenon during use. Summary of the invention
[0005] The purpose of the present invention is to provide a high permeability and selectivity membrane dialyzer and preparation method to solve the problem that the dialyzer in the prior art has limited ability to remove medium and large molecular toxins, and the membrane pore size is too small to effectively remove the medium and large molecular toxins accumulated in the patient's body to adapt to a wide range of patients with different medical needs.
[0006] To achieve the above object, the present invention provides the following technical solutions: The invention provides a high permeability and selectivity membrane dialyzer, comprising the following components in parts by weight: 15 to 35 parts of polyethersulfone, 5 to 40 parts of porogen, 30 to 70 parts of solvent, 3 to 15 parts of additive, and 20 to 60 parts of water; the additive is any one of a swellable additive, hyaluronic acid, and phosphorylcholine.
[0007] Furthermore, the porogen is any one or any combination of polyvinyl pyrrolidone, ethylene glycol, and propylene glycol with a molecular weight of 10,000 to 100,000.
[0008] Furthermore, the solvent is any one or any combination of N-dimethylformamide, N-methylpyrrolidone, and N-dimethylacetamide.
[0009] Furthermore, the expandable additive includes polybetaine, and the polybetaine is phosphobetaine, sulfobetaine or hydroxybetaine.
[0010] The present invention also provides a method for preparing a high permeability and selectivity membrane dialyzer, comprising the following steps: Step 1: Preparation of polymer solution 15-35 parts of polyethersulfone, 30-70 parts of solvent, 5-40 parts of porogen and 1-10 parts of water are stirred evenly at a temperature of 55-85° C. to obtain a polyethersulfone solution; 1-10 parts by weight of an additive is dissolved in 3-15 parts of water and stirred evenly, then slowly poured into the polyethersulfone solution and stirred evenly, and then filtered, defoamed and aged to prepare a uniform spinning solution; Step 2: Dry-wet spinning The spinning solution is transported through the outer annular gap of two high-precision spinnerets with concentric openings, and the hole solution is injected through the inner tube of the rotating nozzle to form the internal pores of the hollow fiber membrane. The spinning solution is extruded and enters a coagulation bath for solidification and forming, and is drawn and wound in a plasticizing bath to obtain a hollow fiber. Step 3: Fiber post-processing The cleaned hollow fibers were immersed in a 0.9% sodium chloride solution and treated in water at 37°C for 2 hours, so that the fibers inside the membrane absorbed the dissolved components in the solution to support the pore structure.
[0011] Furthermore, in step 2, the pore solution comprises 30-60 parts by weight of NN dimethylacetamide and 10-80 parts by weight of pure water, and the coagulation bath is pure water.
[0012] Furthermore, in the step 2, the spinning solution is extruded at a speed of 3-5 ml / min, and the nascent fibers are passed through an air bath of 30-60 cm and then enter a coagulation bath of 40-65° C.
[0013] Furthermore, the hollow fiber treated in step 3 has an inner diameter of 160-220 μm, a membrane wall thickness of 20-50 μm, a membrane pore size of 8-12 nm, a pure water ultrafiltration coefficient of 60-120 ml / h.mmHg, and a maximum transmembrane pressure of 500 mmHg.
[0014] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects: The present invention provides a high-permeability and high-selectivity membrane dialyzer and a preparation method, which can be used for patients with end-stage renal disease and can improve the accumulation of medium and large molecular toxins in long-term dialysis patients. The fiber inner diameter is 160-220 μm, the membrane wall thickness is 20-50 μm, the membrane pore size is 8-12 nm, the pure water ultrafiltration coefficient is 60-120 ml / h.mmHg, and the maximum transmembrane pressure is 500 mmHg. It has good biocompatibility, and has high screening properties for medium and large molecular toxins and controllable albumin loss performance. It is suitable for the treatment of related complications caused by long-term accumulation of medium and large molecules in patients with end-stage renal disease, such as uremic pruritus, restless legs syndrome, long recovery time after dialysis, high incidence of cardiovascular complications, CKD-MBD, anemia, erythropoietin resistance, malnutrition and other related diseases. Specifically: (1) The membrane formation process was optimized and biocompatible swellable additives were introduced during the membrane control stage. These substances were added to the polymer membrane structure, which could improve the membrane permeability through the expansion of the network structure and help form more uniform pores, thereby preparing a new type of dialysis membrane with excellent selectivity and separation performance. It can increase the permeability of water, improve the sieving coefficient of myoglobin, and reduce the sieving coefficient of albumin.
[0015] (2) The pore size homogenization technology was used to pre-treat the membrane by immersing it in 0.9% sodium chloride solution. This improved the pore shrinkage problem during the drying stage to a certain extent. This was mainly due to the interaction of capillary forces. The membrane absorbed the dissolved components through immersion, preventing pore shrinkage during the drying process. This improved the uneven pore structure of the dialysis membrane and adjusted the membrane pore size to be uniformly distributed within the range of 9nm±1nm, thereby achieving effective removal of medium and large molecular toxins. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0017] Figure 1 It is the screening performance of the high permeability and selectivity membrane dialyzer prepared in Example 2 of the present invention; Figure 2 It is a schematic diagram of the connection device of Example 2 of the present invention. DETAILED DESCRIPTION
[0018] The following will combine the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0019] Example 1 18 parts of polyethersulfone, 10 parts of polyvinylpyrrolidone, 60 parts of NN dimethylacetamide, and 6 parts of water are added to a reactor with temperature control and stirring functions, and stirred at a temperature of 55-85°C for 24 hours. In another container, 3 parts of polybetaine are dissolved in 8 parts of water, stirred evenly at room temperature, and then slowly poured into the polyethersulfone solution, stirred for about 2 hours until the solution is uniform, and then filtered, degassed and aged to obtain the spinning solution. The spinning solution and the core liquid are extruded through the outer ring seam and inner hole of two concentrically opened high-precision spinnerets, and the spinning speed is controlled to be 5 ml / min. The nascent fiber passes through an air bath with a height of 40 cm and then enters a coagulation bath with a temperature of 55°C for curing and forming, and then is stretched and wound in a plasticizing bath. The core liquid contains 48 parts by weight of NN dimethylacetamide and 62 parts by weight of pure water, and the coagulation bath is pure water. The simulated hollow fiber membrane undergoes several water washing processes, and then undergoes a 2-hour pretreatment with 0.9% sodium chloride, and then is dried in a high-temperature drying oven and collected by a hexagonal collecting wheel.
[0020] Example 2 The hollow fiber membrane of Example 1 is loaded into the shell by using the existing mature production process to make a finished dialyzer. After the product is sterilized, its screening performance is tested. The test liquid should be anticoagulated bovine plasma with a protein concentration of (60±5) g / l, to which 2-6 mg β2-microglobulin, 10-40 mg myoglobin, and 3-10 mg inulin are added. Figure 2Connection method: Connect the device to test the screening coefficient.
[0021] Calculation of the screening coefficient: Collect blood inlet and outlet samples, test sample concentration, and calculate the clearance rate according to the following formula: Where: S refers to the screening coefficient; C F Refers to the filtrate concentration; C BI Refers to blood inlet concentration; C BO Refers to the blood outlet concentration; In the formula, C F , C BI , C BO The concentration units used are the same, and the allowable error of measurement is ±0.1.
[0022] The test results of the screening coefficient are as follows: Figure 1 shown.
[0023] Example 3 35 parts of polyethersulfone, 5 parts of polyvinylpyrrolidone, 70 parts of NN dimethylacetamide, and 6 parts of water are added to a reactor with temperature control and stirring functions, and stirred at a temperature of 55-85°C for 24 hours. In another container, 3 parts of polybetaine are dissolved in 8 parts of water, stirred evenly at room temperature, and then slowly poured into the polyethersulfone solution, stirred for about 2 hours until the solution is uniform, and then filtered, degassed and aged to obtain the spinning solution. The spinning solution and the core liquid are extruded through the outer ring seam and inner hole of two concentrically opened high-precision spinnerets, and the spinning speed is controlled to be 5 ml / min. The nascent fiber passes through an air bath with a height of 40 cm and then enters a coagulation bath with a temperature of 55°C for curing and forming, and then is stretched and wound in a plasticizing bath. The core liquid contains 48 parts by weight of NN dimethylacetamide and 62 parts by weight of pure water, and the coagulation bath is pure water. The simulated hollow fiber membrane undergoes several water washing processes, and then undergoes a 2-hour pretreatment with 0.9% sodium chloride, and then is dried in a high-temperature drying oven and collected by a hexagonal collecting wheel.
[0024] Example 4 18 parts of polyethersulfone, 10 parts of polyvinylpyrrolidone, 60 parts of NN dimethylacetamide, and 6 parts of water are added to a reactor with temperature control and stirring functions, and stirred at a temperature of 55-85°C for 24 hours. In another container, 3 parts of sulfobetaine are dissolved in 8 parts of water, stirred evenly at room temperature, and then slowly poured into the polyethersulfone solution, stirred for about 2 hours until the solution is uniform, and then filtered, degassed and aged to obtain the spinning solution. The spinning solution and the core liquid are extruded through the outer ring seam and inner hole of two concentrically opened high-precision spinnerets, and the spinning speed is controlled to be 5 ml / min. The nascent fiber passes through an air bath with a height of 40 cm and then enters a coagulation bath with a temperature of 55°C for curing and forming, and then is stretched and wound in a plasticizing bath. The core liquid contains 48 parts by weight of NN dimethylacetamide and 62 parts by weight of pure water, and the coagulation bath is pure water. The simulated hollow fiber membrane undergoes several water washing processes, and then undergoes a 2-hour pretreatment with 0.9% sodium chloride, and then is dried in a high-temperature drying oven and collected by a hexagonal collecting wheel.
[0025] Example 5 18 parts of polyethersulfone, 10 parts of polyvinylpyrrolidone, 5 parts of ethylene glycol, 5 parts of propylene glycol, 60 parts of NN dimethylacetamide, and 6 parts of water are added to a reactor with temperature control and stirring functions, and stirred at a temperature of 55-85°C for 24 hours. In another container, 3 parts of polybetaine are dissolved in 8 parts of water, stirred evenly at room temperature, and then slowly poured into the polyethersulfone solution, stirred for about 2 hours until the solution is uniform, and then filtered, degassed and aged to obtain the spinning solution. The spinning solution and the core liquid are extruded through the outer ring seam and inner hole of two concentrically opened high-precision spinnerets, and the spinning speed is controlled to be 5 ml / min. The nascent fiber passes through an air bath with a height of 40 cm and then enters a coagulation bath with a temperature of 55°C for curing and forming, and then is stretched and wound in a plasticizing bath. The core liquid contains 48 parts by weight of NN dimethylacetamide and 62 parts by weight of pure water, and the coagulation bath is pure water. The simulated hollow fiber membrane undergoes several water washing processes, and then undergoes a 2-hour pretreatment with 0.9% sodium chloride, and then is dried in a high-temperature drying oven and collected by a hexagonal collecting wheel.
[0026] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A high permeability and selectivity membrane dialyzer, characterized in that: The invention comprises the following components in parts by weight: 15 to 35 parts of polyethersulfone, 5 to 40 parts of porogen, 30 to 70 parts of solvent, 3 to 15 parts of additive and 20 to 60 parts of water; the additive is any one of a swellable additive, hyaluronic acid and phosphorylcholine.
2. The high permeability and selectivity membrane dialyzer according to claim 1, characterized in that: The porogen is any one or any combination of polyvinyl pyrrolidone, ethylene glycol, and propylene glycol with a molecular weight of 10,000 to 100,000.
3. The high permeability and selectivity membrane dialyzer according to claim 1, characterized in that: The solvent is any one or any combination of N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylacetamide.
4. The high permeability and selectivity membrane dialyzer according to claim 1, characterized in that: The swellable additive includes polybetaine, which is phosphobetaine, sulfobetaine or hydroxybetaine.
5. The method for preparing a high permeability and selectivity membrane dialyzer according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Preparation of polymer solution 15-35 parts of polyethersulfone, 30-70 parts of solvent, 5-40 parts of porogen and 1-10 parts of water are stirred evenly at a temperature of 55-85° C. to obtain a polyethersulfone solution; 1-10 parts by weight of an additive is dissolved in 3-15 parts of water and stirred evenly, then slowly poured into the polyethersulfone solution and stirred evenly, and then filtered, defoamed and aged to prepare a uniform spinning solution; Step 2: Dry-wet spinning The spinning solution is transported through the outer annular gap of two high-precision spinnerets with concentric openings, and the hole solution is injected through the inner tube of the rotating nozzle to form the internal pores of the hollow fiber membrane. The spinning solution is extruded and enters a coagulation bath for solidification and forming, and is drawn and wound in a plasticizing bath to obtain a hollow fiber. Step 3: Fiber post-processing The cleaned hollow fibers were immersed in a 0.9% sodium chloride solution and treated in water at 37°C for 2 hours, so that the fibers inside the membrane absorbed the dissolved components in the solution to support the pore structure.
6. The method for preparing a high permeability and selectivity membrane dialyzer according to claim 5, characterized in that: In the step 2, the pore solution comprises 30-60 parts by weight of a solvent and 10-80 parts by weight of pure water, and the coagulation bath is pure water.
7. The method for preparing a high permeability and selectivity membrane dialyzer according to claim 5, characterized in that: The spinning solution extrusion condition in step 2 is controlled at a speed of 3-5 ml / min, and the nascent fiber enters a coagulation bath at 40-65° C. after passing through an air bath of 30-60 cm.
8. The method for preparing a high permeability and selectivity membrane dialyzer according to claim 5, characterized in that: The hollow fiber treated in step 3 has an inner diameter of 160-220 μm, a membrane wall thickness of 20-50 μm, a membrane pore size of 8-12 nm, a pure water ultrafiltration coefficient of 60-120 ml / h.mmHg, and a maximum transmembrane pressure of 500 mmHg.